المشكلات الاجتماعیة لذوي الاحتیاجات الخاصة (المسنین) دراسة میدانیة في مدینة بغداد (Journal of the College of Education for Women, 2019)
The present study deals with the social work and the social problems whichthe Elderly who lives in the house of special needs suffer from . this study aims toshed light to the most important social problems which they suffer from inside andshow their relationship and interaet with each ofher and what we can see about thatintereact either negative or positive relationship . Its scientific importance includeadding a new study in the field of take care of the Elderly . and that will enrich thescientific field with agood knowledge . Becouse the studies in this part was little ,but the scientific and practical importance of this study presents by the results andspecify of the important problems . In addition to that we can knew about thenature of their relationship and their interact with each other and in the other handhow is their relationship with the administration and the other worker concerningthe social research and present the recommendations to tuckle it and redueed itsnegative results . All that will give us agood result in planning and developmenteither in the social , psychological , and healthy aspect of the Elderly this studyincludes the introduction which includes identifying the problems , the gool , itsscientific and practical importance . In addition to that the reason fer choice thissubject . then , the second chaptere includes Conceptions and previous studies . thethird chapter presents the results of the study . And finally , the fourth chaptershows the conclusions and recommendations and attached and Abstract in EnglishLanguage .